New approaches to assess and improve ship operating performance - Thai Gia Tran; Hyun Cheol Kim (International Journal of Naval Architecture and Ocean Engineering)
The deterioration in the technical conditions of the main engine, hull, and propeller over time in service is natural and causes adverse effects on ship operating performance, so determining and overcoming this phenomenon is necessary. However, effectively solving this problem is not simple because it is affected by many complex and random factors such as engine deterioration, increased roughness of hull and propeller surfaces, changes in sea state and ship load, etc. In this study, our new approach based on the black-box method and detailed propeller diagrams provides an effective way to assess and improve ship performance both under specific operating conditions and after a period of service. This method was verified and validated with the test data of the Glory Star oil tanker and applied to the Duong River dry cargo ship in Vietnam to determine its performance degradation and provide solutions to overcome this problem. The results showed that after 5 years out of dry dock, the study ship's performance or propulsion efficiency was reduced by about 8.6%, resulting in an increase in fuel consumption of about 6.5% and a decrease in ship speed of about 14.7%. By applying technical solutions such as tuning the engine operating mode and choosing a practical propeller design point, the performance of this ship was greatly improved and brought about high economic and technical efficiency. Especially, the cutting of the propeller edges not only solved the torque-rich phenomena occurring on the study ship's main engine after 5 service years, but also saved 5.1% and 4.9% in hourly fuel consumption, and increased 3.9% and 4.9% in ship speed, calculated for ballast and full load sea trials, respectively.